Multiplicative or compensatory advantage? Multigenerational contribution to grandchildren's educational success in the Soviet and the post-Soviet contexts. Issue 2 (15th March 2023) - Helemäe, Jelena; Saar, Ellu
ABSTRACT: Drawing on retrospective data from the Estonian Family and Fertility Survey, this article examines the impact of grandfathers, who reached adulthood in the Estonian Republic before World War II, on their grandchildren's educational attainment in the late Soviet and post-Soviet Estonia. The article argues that despite the Sovietization policies, the high social position of grandfathers had a positive effect on their grandchildren's educational attainment, net of parental education and resources. Our results show that the multiplication effect (i.e. the advantage of having highly educated parents is strengthened by grandparents' resources) prevails over the compensatory one (i.e. the use of advantageous grandparents' resources to overcome shortage of parental resources), suggesting that social hierarchies and advantages of the pre-Soviet period contribute to the overall and increasing intergenerational inequality in the late Soviet and post-Soviet Estonian society. This conclusion is also supported by finding that respondents with persistently high (across two familial generations and political regimes) social background have the highest probability to attain higher education, while offspring of parents characterized by the loss of grandparents' high pre-WWII status has very low (and practically non-different from that of descendants of persistently low social background) probability to attain higher education.